REAKSI PASAR TERHADAP PENGUMUMAN RIGHT ISSUE PADA PERUSAHAAN WARRANT ISSUER DAN NON WARRANT ISSUER - Susanti, Putu Adi; Ardiana, Pt Agus (E-Jurnal Akuntansi, 2014)
This research aims at testing the containing information within the announcement of right issue phenomenon at the companies of warrant issuer and non-warrant issuer at Indonesia Stock Exchange in the period of observation from 2008 until 2012. It used event study for the technique of analysis, one sample T-test and independent sample T-test. The result showed that the announcement of right issue phenomenon does not contain information either for the entire emiten sample or for emiten sample which announced right issue without warrant and with warrant. It also discovered that there is no return abnormal difference among the companies which announced right issue without warrant and those ones with warra nt.
Keywords: market reaction, abnormal return, rights issue, warrant.